2021
DOI: 10.3389/fgene.2021.610291
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Proteins Play an Important Role in the Prognosis of Patients With Testicular Germ Cell Tumor

Abstract: Testicular germ cell tumors (TGCTs) are common urological neoplasms in young adult males. The outcome of TGCT depends on pathologic type and tumor stage. RNA-binding proteins (RBPs) influence numerous cancers via post-transcriptional regulation. The prognostic importance of RBPs in TGCT has not been fully investigated. In this study, we set up a prognostic risk model of TGCT using six significantly differentially expressed RBPs, namely, TRMT61A, POLR2J, DIS3L2, IFIH1, IGHMBP2, and NPM2. The expression profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…At present, the research on the NPM family mainly focuses on NPM1, and there is a lack of related reports on NPM2. Only a few experiments have shown that the expression or deletion of NPM2 is related to the occurrence, development, prognosis, and outcome of tumors [ 23 26 ]. Therefore, the exploration of NPM2 may bring new breakthroughs in the field of MPM diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the research on the NPM family mainly focuses on NPM1, and there is a lack of related reports on NPM2. Only a few experiments have shown that the expression or deletion of NPM2 is related to the occurrence, development, prognosis, and outcome of tumors [ 23 26 ]. Therefore, the exploration of NPM2 may bring new breakthroughs in the field of MPM diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, abnormal expression of NDUFAF7 could lead to mitochondrial dysfunction that might contribute to the development of myositis, especially IMNM 23,24 . POLR2J is a DNA repair gene that, through post‐transcriptional regulation, affects a variety of cancers, including rectal tumors and testicular germ cell tumors 25,26 . CD99 is a transmembrane glycoprotein shown to be upregulated in various malignancies and is also crucial for peripheral immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 POLR2J is a DNA repair gene that, through post-transcriptional regulation, affects a variety of cancers, including rectal tumors and testicular germ cell tumors. 25,26 CD99 is a transmembrane glycoprotein shown to be upregulated in various malignancies and is also crucial for peripheral immune responses. It regulates a step at or close to the end trans-endothelial migration of polymorphonuclear leukocytes 27 and present to be a promising therapeutic target in acute myeloid leukemia.…”
Section: Gsea Of Key Genes In Imnmmentioning
confidence: 99%
“…Meanwhile, RPB3 is a crucial subunit of RNA polymerase II that can interact with ATF4 and enhance the activation of ATF4 by promoter recognition [11]. Interestingly, POLR2J is considered as a promising prognostic biomarker for patients with testicular germ cell tumor [12]. Meanwhile, POLR2J is also overexpressed in rectal tumor organoids compared with than normal rectum organoids [13].…”
Section: Introductionmentioning
confidence: 99%